2022
DOI: 10.3390/bios12121082
|View full text |Cite
|
Sign up to set email alerts
|

Potential Environmental and Health Implications from the Scaled-Up Production and Disposal of Nanomaterials Used in Biosensors

Abstract: Biosensors often combine biological recognition elements with nanomaterials of varying compositions and dimensions to facilitate or enhance the operating mechanism of the device. While incorporating nanomaterials is beneficial to developing high-performance biosensors, at the stages of scale-up and disposal, it may lead to the unmanaged release of toxic nanomaterials. Here we attempt to foster connections between the domains of biosensors development and human and environmental toxicology to encourage a holist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 346 publications
0
3
0
Order By: Relevance
“…Research on the toxicity of engineered NPs is still in development. Specifically, there is a significant knowledge gap regarding the potential environmental impacts of MoS 2 NPs applied in novel technologies [25]. In this study, 2D MoS 2 NPs or bulk MoS 2 did not significantly affect the adult survival of E. crypticus (p > 0.05; Figure 2A) or F. candida (p > 0.05; Figure 2C) across all tested concentrations.…”
Section: Adult Survival and Reproductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Research on the toxicity of engineered NPs is still in development. Specifically, there is a significant knowledge gap regarding the potential environmental impacts of MoS 2 NPs applied in novel technologies [25]. In this study, 2D MoS 2 NPs or bulk MoS 2 did not significantly affect the adult survival of E. crypticus (p > 0.05; Figure 2A) or F. candida (p > 0.05; Figure 2C) across all tested concentrations.…”
Section: Adult Survival and Reproductionmentioning
confidence: 59%
“…NPs have unique physical properties distinct from the properties of their corresponding bulk forms due to increased relative surface area per volume unit and the dominance of quantum effects [25]. As the size decreases, the surface energy of the particles is expected to increase, which normally results in enhanced dissolution and solubility of NPs as compared to the bulk form [44].…”
Section: Nanoparticle Versus Bulk Effects-an Overviewmentioning
confidence: 99%
“…Considering the importance of wastewater discharges, several studies have revealed strategies to reduce toxic effects from nanomaterials synthesis that directly affect both human health and the environment. Alternatives to traditional techniques for the reuse and recycling of nanoparticles have been discussed, which involve centrifugation and solvent evaporation . Recent studies have demonstrated that the use of eco-friendly routes during the production of nanoparticles is necessary to neutralize the nanoparticle waste before disposal .…”
Section: Resultsmentioning
confidence: 99%
“…Alternatives to traditional techniques for the reuse and recycling of nanoparticles have been discussed, which involve centrifugation and solvent evaporation. 47 Recent studies have demonstrated that the use of eco-friendly routes during the production of nanoparticles is necessary to neutralize the nanoparticle waste before disposal. 48 Green alternatives to produce MNPs based on the benefits of microbes use such as bacteria, microalgae, yeast, actinomycetes, and fungi have also been reported to carry out responsible industrial production.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This approach also opens up wide possibilities for the scalability of the production of low-cost sensors. However, one should also remember about the dangers of mass-production and the disposal of nanomaterials [ 149 ]. The synthesis and application of more complex materials, which combine the advantages of few components, such as polymer–carbon nanomaterial composites, still remain a topic of research that gives room for further development [ 150 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%